(untitled) (Eurasian Journal of Humanities and Social Sciences, 2026)
This article examines the linguacultural peculiarities of tribal languages from a comparative and descriptive perspective. Tribal languages reflect unique worldviews shaped by cultural traditions, social structures, and environmental conditions. The study aims to analyze how language and culture interact in tribal communities and how linguistic structures encode cultural meanings. Using a linguacultural approach, the research explores lexical, semantic, and pragmatic features that distinguish tribal languages from standardized languages. The findings show that tribal languages preserve cultural identity through metaphorical expressions, oral traditions, kinship terminology, and nature-based conceptualization. The study concludes that tribal languages serve as both communicative systems and cultural memory carriers